Crayons rock! - Dean, Kim, 1969-; Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
Pete the cat learns not to give up on his love of drawing with crayons.
School Library Journal
School Library Journal, October 2020
2.1
K-3
K-3
Keywords: Animals -- Juvenile fiction; Cats -- Juvenile fiction; Crayon drawing -- Juvenile fiction; Friendship -- Juvenile fiction; Animals -- Fiction; Cats -- Fiction; Crayon drawing -- Fiction; Friendship -- Fiction; Animals -- Fiction; Cats -- Fiction; Crayon drawing -- Fiction; Friendship -- Fiction; Picture books